2003
DOI: 10.1029/2002jd003021
|View full text |Cite
|
Sign up to set email alerts
|

Depositional characteristics of 7Be and 210Pb in southeastern Michigan

Abstract: [1] The depositional fluxes in the bulk and dry fallout as well as the concentrations of 7 Be and 210 Pb in aerosols were measured for a period of 17 months at Detroit, Michigan. The bulk depositional fluxes of 7 Be and 210 Pb varied between 3.11 and 63.0 dpm cm À2 yr À1 (mean of 11.4 dpm cm À2 yr À1 ) and 0.35 and 10.3 dpm cm À2 yr À1 (mean of 1.41 dpm cm À2 yr À1 ), respectively, and this variability in the depositional fluxes is attributed to the frequency and amount of precipitation and seasonal variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
104
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 43 publications
21
104
2
1
Order By: Relevance
“…McNeary and Baskaran, 2003). Even considering a first-order linear relationship between 210 Pb inventories and annual precipitations and that the y-intercept is negative (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…McNeary and Baskaran, 2003). Even considering a first-order linear relationship between 210 Pb inventories and annual precipitations and that the y-intercept is negative (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The daily precipitation (mm d -1 ) was calculated according to the total rainfall and collection time. The average precipitation (mm d -1 ) and deposition flux (Bq m -2 d -1 ) of 7 Be in each month were calculated based on the monthly integrated equation (McNeary and Baskaran, 2007) and the specific days in each month:…”
Section: Methodsmentioning
confidence: 99%
“…Seasonal 7 Be deposition fluxes measured in Germany (Thomas Steinkopff, German Weather Service, private communication), Switzerland (Heikkilä et al, 2008a), United States (McNeary and Baskaran, 2003) and Japan (Igarashi et al, 1998) are shown in Fig. 4.…”
Section: Surface Air Concentrations and Deposition Fluxesmentioning
confidence: 99%